2014
DOI: 10.1002/per.1954
|View full text |Cite
|
Sign up to set email alerts
|

Materialism and Well–Being in the Uk and Chile: Basic Need Satisfaction and Basic Need Frustration as Underlying Psychological Processes

Abstract: A growing body of evidence shows that materialistic values are linked to lower well-being. Selfdetermination theory offers an explanation through the low fulfilment of the basic psychological needs for autonomy, competence, and relatedness. However, recent research suggests that frustration of these psychological needs may also play an additional role. Using structural equation modelling in adult samples from an established massconsumer society (UK: N = 958) and a fast-developing new economy (Chile: N = 257) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 83 publications
(177 reference statements)
5
81
0
2
Order By: Relevance
“…Following Kasser and Ryan's (1996) contention that it is the relative importance of intrinsic and extrinsic values in relation to an individual's value system that is important, we calculated an intrinsic relative to extrinsic values score (I/E score) using the same method as Duriea, Vansteenkiste, Soenens, and De Witte (2007), and Unanue, Dittmar, Vignoles, and Vansteenkiste (2014). Namely, we first subtracted an individual's over mean score on all values from each individual score.…”
Section: Methodsmentioning
confidence: 99%
“…Following Kasser and Ryan's (1996) contention that it is the relative importance of intrinsic and extrinsic values in relation to an individual's value system that is important, we calculated an intrinsic relative to extrinsic values score (I/E score) using the same method as Duriea, Vansteenkiste, Soenens, and De Witte (2007), and Unanue, Dittmar, Vignoles, and Vansteenkiste (2014). Namely, we first subtracted an individual's over mean score on all values from each individual score.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has indicated that need satisfaction relates to multiple well‐being outcomes, including vitality, life satisfaction, and positive affect (e.g., Bartholomew, Ntoumanis, Ryan, Bosch, & Thøgersen‐Ntoumani, ). In contrast, need frustration has consistently been related to maladaptive outcomes, including emotional exhaustion (e.g., Van den Broeck, De Witte, Lens, & Vansteenkiste, ), depressive symptoms (Bartholomew et al, ), and physical symptoms (Unanue, Dittmar, Vignoles, & Vansteenkiste, ). Such findings have been obtained using both self‐reports and ratings of adjustment (e.g., Ahmad, Vansteenkiste, & Soenens, ) and held in both correlational and experimental designs (e.g., Weinstein, Khabbaz, & Legate, ).…”
Section: Introductionmentioning
confidence: 99%
“…Por ejemplo, individuos con mayores niveles de bienestar subjetivo tienden a mostrar mejores indicadores de salud mental y física, a construir relaciones más duraderas y significativas, a ser más cooperadores, a tener menos prejuicios, a ser más caritativos y a mostrar mayores niveles de comportamiento pro-social y de preocupación por otros/as (Adler y Seligman, 2016;Diener y Tay, 2012). Por otro lado, también se ha encontrado que el bienestar subjetivo predice la protección del medioambiente, lo que ayudaría a la sostenibilidad planetaria (Brown y Kasser, 2005;Unanue et al, 2014).…”
Section: Hacia Un Nuevo Modelo De Desarrollo Basado En Bienestar: Elunclassified